Maximizing Workshop Efficiency Reusing Old Compressors Globally: Memaksimalkan Efisiensi Bengkel Menggunakan Kembali Kompresor Lama Secara Global - Kurniawan, Bagus; Mulyadi (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the feasibility of repurposing old refrigerator compressors to construct an air compressor for workshop use. Conducted at the Laboratory of Mechanical Engineering, Muhammadiyah University of Sidoarjo, the research assesses performance factors such as compressor tube filling time and injection settings. Results indicate that using one compressor motor takes 12 minutes and 57 seconds to fill the tube, while two motors reduce this to 8 minutes and 12 seconds, reaching a maximum pressure of 75 psi. Higher spray gun settings result in faster air depletion. Although pressure output is weaker compared to conventional compressors, the cost-effectiveness of using reused materials is evident, highlighting potential economic and environmental benefits. Highlight: Repurposing old compressors for workshop air supply. Assessing performance: filling time, injection settings. Cost-effective, eco-friendly solution for workshop equipment. Keyword: Repurposing, Refrigerator Compressors, Workshop Equipment, Performance Assessment, Cost-effectiveness